2007
DOI: 10.1016/j.jhse.2007.03.015
|View full text |Cite
|
Sign up to set email alerts
|

A Self-Administered Questionnaire for Basal Osteoarthritis of the Thumb

Abstract: Basal osteoarthritis of the thumb is a common condition for which numerous operations have been proposed without any particular one having been shown to be superior. One of the problems in evaluating the results of surgery is that there is no validated outcome score specifically for the condition. The purpose of this study was to construct a self-administered questionnaire (the Nelson score) to assess the outcome following surgery for this condition and to test its properties. Correlating the questionnaire sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 28 publications
0
31
0
Order By: Relevance
“…The scoring systems used were the QuickDASH, 7 the patient-related wrist evaluation (PRWE) 8 and Nelson base of thumb arthritis scores. 9 QuickDASH is a fully validated hand and wrist score, and the Nelson score is a validated diseasespecific score for base of thumb arthritis. All tightrope suspensionplasty operations were performed by a single surgeon in our department (TS) using the technique described below.…”
Section: Data Collectionmentioning
confidence: 99%
“…The scoring systems used were the QuickDASH, 7 the patient-related wrist evaluation (PRWE) 8 and Nelson base of thumb arthritis scores. 9 QuickDASH is a fully validated hand and wrist score, and the Nelson score is a validated diseasespecific score for base of thumb arthritis. All tightrope suspensionplasty operations were performed by a single surgeon in our department (TS) using the technique described below.…”
Section: Data Collectionmentioning
confidence: 99%
“…Citron et al also found that their validated Nelson Hospital Score, specifically developed to assess recovery after surgery in patients with TMC arthrosis, poorly correlated with grip strength but moderately correlated with key pinch strength. 12 The TASD questionnaire was expected to show at least a moderate correlation with depression as it did as previous studies showed a correlation between the DASH or QuickDASH and depression in patients with symptomatic TMC arthrosis. 4,25,29,33 In addition, the TASD was expected to show a stronger correlation with self-efficacy than it did as the QuickDASH and pain self-efficacy strongly correlated in patients with other common hand conditions.…”
Section: Discussionmentioning
confidence: 90%
“…The AUSCAN Osteoarthritis Hand Index score is significantly more responsive for patients with TMC arthrosis alone than for patients with additional involvement of other osteoarthritic hand joints. 28 Although Citron et al developed the Nelson Hospital Score, a TMC arthrosisspecific questionnaire, its goal was to assess symptoms and disability after surgery, 12 and has not been validated for use with general TMC arthrosis patients. In addition, the Nelson Hospital Score has poor methodological quality, 31 lacks factor analysis to confirm the number of factors (subscales) and related items, and has rarely been used.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As yet, widely used tools for the assessment of treatment effects to conservative therapies in thumb base OA are generally not condition specific. Such tools have been developed and tested to assess outcome following hand surgery in order to better detect variations related to treatment while considering the common coexistence of other hand conditions in the same individual . Furthermore, efforts are currently underway to develop new classification criteria for hand OA distinguishing thumb base OA from IP OA in order to reduce heterogeneity in clinical trials.…”
Section: Discussionmentioning
confidence: 99%